Effect of Auxins and Activated Carbon on In Vitro Rooting of Two Blueberry Cultivars (Vaccinium corymbosum) - Zalt Najla; Yasmin Samina; Hamakhan Awara M.; Polat Şule; Yu Hong; Ge Chunfeng; Imrak Burhanettin; Kafkas Ebru (Journal of Horticultural Research)
The optimization of tissue culture protocols for blueberry propagation is crucial to meet the increasing demand for disease-free planting materials. This study aimed to determine the effects of three auxins (IBA, IAA, and NAA) at different concentrations to enhance root and shoot development of two blueberry cultivars with different abilities to root, ‘Lanmei #1’and ‘Brightwell’. Results showed that NAA at 0.5 mg·L−1 significantly promoted shoot number and length in ‘Lanmei #1’ while ‘Brightwell’ showed a limited response. IAA had a variable impact on both shoot and root parameters, with ‘Lanmei #1’ showing more pronounced positive responses. IBA showed a differential response on root and shoot parameters in both cultivars, with ‘Lanmei #1’ showing a superior response for shoot number, length, root length, and overall plant vigor. Activated carbon had minimal effect on growth parameters across both cultivars. ‘Lanmei #1’ demonstrated a robust response to auxin treatments, suggesting it is more suitable for in vitro rooting. The present results confirm previous data on the different abilities of blueberry genotypes to root and the necessity of optimizing the rooting protocol depending on the cultivar.